Comparative Estimation Of The Distribution Destinations Cost Of The Republican Budget (Journal of Economic Research & Business Administration, 2016)
This paper examines the distribution of the national budget cost byfunctional groups and budget programs, comparative evaluation of theirchanges. On the basis of forecast data are studied the amount and structureof costs by years of three-year budgets for 2015-2017 and 2016-2018, thetendencies and directions of financing the budget programs, as well as setthe volume ratio of the forecast of financing from various budget programs.Some of the factors and conditions of changes in the approved budgetwere identified, which justified the changes and additions that are madeeach year to the tax legislation, as well as inefficient and inappropriateuse of budget programs administrators of budget funds allocated, whichalso worsen the state budget planning. There also operate at a higher costof the state related to its acquisition of financial assets, becouse the cost,ultimately, increase the budget deficit.
Keywords: Republican budget; cost of the republican budget; expenses of the republican budget; the budget programs; financing of budget programs; budget loans; the cost of acquisition of financial assets.